2020
DOI: 10.3906/sag-2003-127
|View full text |Cite
|
Sign up to set email alerts
|

BMP and TGFβ use and release in bone regeneration

Abstract: A fracture that does not unite in nine months is defined as nonunion. Nonunion is common in fragmented fractures and large bone defects where vascularization is impaired. The distal third of the tibia, the scaphoid bone or the talus fractures are furthermore prone to nonunion. Open fractures and spinal fusion cases also need special monitoring for healing. Bone tissue regeneration can be attained by autografts, allografts, xenografts and synthetic materials, however their limited availability and the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 76 publications
(233 reference statements)
0
18
0
1
Order By: Relevance
“…Its use has led to results comparable to those of autologous grafts in terms of bone volume and density and even reduced the risk of infection and the time of hospitalization [ 113 ]. It has been reported that bone repair could be produced by BMP-2, but this ability is dose-dependent [ 114 ], while a high dosage could give unwanted effects [ 115 , 116 ]. In the tooth matrix, the BMP is found in physiological quantities and therefore adequate for the patient.…”
Section: Bone Substitutes and Graftmentioning
confidence: 99%
“…Its use has led to results comparable to those of autologous grafts in terms of bone volume and density and even reduced the risk of infection and the time of hospitalization [ 113 ]. It has been reported that bone repair could be produced by BMP-2, but this ability is dose-dependent [ 114 ], while a high dosage could give unwanted effects [ 115 , 116 ]. In the tooth matrix, the BMP is found in physiological quantities and therefore adequate for the patient.…”
Section: Bone Substitutes and Graftmentioning
confidence: 99%
“…По данным разных литературных источников, вероятность иммунной реакции после имплантации таких материалов составляет около 10% [9]. Деминерализованный костный матрикс (ДМК) -это высокоочищенный, производный аллогенной кости, материал, лишенный (более чем на 40%) минерального компонента при сохранении коллагена и неколлагеновых белков-индукторов [10], определяющих остеоиндуктивность. Обладая пластичностью и высокой степенью биодеградации в сравнении с недеминерализованными костными материалами, процесс остеоинтеграции и ремоделирования имплантированного ДМК происходит интенсивнее [4].…”
Section: аллогенные костные материалыunclassified
“…The human genome contains more than 20 types of heterodimer or homodimer BMPs. According to the sequence homology of their amino acids, structures, and functions, they are divided into four separate subfamilies: (1) BMP2 and 4; (2) BMP5, 6, 7, 8a, and 8b; (3) BMP9 and 10; and (4) BMP12, 13, 14 (Bal et al, 2020 ). BMPs are involved in biological activities such as embryogenesis (epidermal induction and inhibiting ectodermal fate), developmental processes (cell proliferation, differentiation, and apoptosis), and also the maintenance of adult tissue homeostasis (Wang et al, 2014 ; Biniazan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2) BMP5,6,7,8a,and 8b; (3) BMP9 and 10; and (4) BMP12, 13, 14 (Bal et al, 2020). BMPs are involved in biological activities such as embryogenesis (epidermal induction and inhibiting ectodermal fate), developmental processes (cell proliferation, differentiation, and apoptosis), and also the maintenance of adult tissue homeostasis (Wang et al, 2014;Biniazan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%